The Impact of Transformational Leadership on Teacher Motivation and Student Achievement (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
This research explores the correlation between transformational leadership styles in school administrators and teacher motivation levels. It investigates how motivated teachers influence student achievement outcomes and whether transformational leadership plays a key role in fostering this connection.